Problem Gambling Features and Gendered Gambling Domains Amongst Regular Gamblers in a Swedish Population-Based Study - Svensson, Jessika (Springer US, 2014)
This study aimed to investigate, from a gender perspective, how different features of problem gambling present in men and women who gamble regularly in Sweden were distributed in four domains based on gambling type (chance or strategy) and setting (public or domestic). Problem gambling features were based on the nine items in the Problem Gambling Severity Index (PGSI). It was hypothesized that men and women gamble in different domains. Further, it was hypothesized that male gamblers overall experienced more problems with gambling than female gamblers, although in the same domains they would report the same level of problems. A further hypothesis predicted that regular female gamblers would experience more health and social problems and men would experience more financial difficulties. Interviews with a subsample of gamblers (n = 3191) from a Swedish nationally representative sample (n = 8179) was used to examine how features of problem gambling correspond with gender and the domains. Only the first hypothesis was fully supported. Men were more likely to participate in forms of gambling requiring strategy in a public setting, and women were more likely to participate in chance-based gambling in a domestic setting. Male and female gamblers had similar levels of problem gambling in the bi-variate analysis, but if controlling for age and gambling in multiple domains, women were more at risk than men. Additionally, men and women presented similar health and economic situations. The differences between male and female gamblers in Sweden have implications for research and prevention.